Tata Kelola Perusahaan dan Leverage Terhadap Financial Distress Di Bursa Efek Indonesia - Go, Owen Tamashi; Wijaya, Liliana Inggrit; Muhardi, Werner Ria (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
By developing a bankruptcy model with data from non-financial sector businesses registered on IDX for the years 2017"“2021, this research seeks to explore the impact of corporate governance and leverage. A quantitative method with a logistic regression model was applied. The final sample contained of 349 firms from the non-financial sector, with 1745 observations. According to the findings, leverage, institutional ownership, and board size are variables that the model takes into account. Meanwhile, managerial ownership, independent commissioner, firm size, and firm growth have no significant effect. Although not all variables included in the model are significant, insignificant variables are still present to improve the prediction model's accuracy. The findings revealed that this destruction model was 75.6% accurate.